2012
DOI: 10.1134/s1068162012050044
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of novel terpenophenol-chlorin conjugates and evaluation of their membranotropic and membrane-protecting properties

Abstract: A series of terpenophenol-chlorin conjugates where terpenophenolic fragment has amide bond with macrocycle of methylpheophorbide a, formed by amidation of 13(2)-ester group were obtained by interaction of methylpheophorbide a and ortho-aminomethyl derivatives of 2-isobornyl-4-methylphenol. The substances investigated ability to interact with the cell membrane was shown in blood erythrocytes surface structure with scanning electron microscope. The conjugates studied were established to have antioxidant and memb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 24 publications
1
2
0
1
Order By: Relevance
“…The highest MPA was observed in compound 7 with a phenyl substituent. A similar dependence was revealed in the study of MPA terpenophenol-chlorin conjugates (Belykh et al, 2012). For the studied compounds, MPA declined with decreasing length and volume of the hydrocarbon fragment: (octyl)> (hexyl)> (butyl), which is due to the peculiarities of the interaction of these compounds with the erythrocyte membrane, studied by scanning electron microscopy.…”
Section: Antioxidant Activitysupporting
confidence: 76%
“…The highest MPA was observed in compound 7 with a phenyl substituent. A similar dependence was revealed in the study of MPA terpenophenol-chlorin conjugates (Belykh et al, 2012). For the studied compounds, MPA declined with decreasing length and volume of the hydrocarbon fragment: (octyl)> (hexyl)> (butyl), which is due to the peculiarities of the interaction of these compounds with the erythrocyte membrane, studied by scanning electron microscopy.…”
Section: Antioxidant Activitysupporting
confidence: 76%
“…[14][15][16] 2-Изоборнил-4-метилфенол (6) и 2-трет-бутил-6-изоборнил-4-метилфенол (8) получали по реакции алкилирования п-крезола и 2-трет-бутил-4-метилфенола камфеном; [17,18] 2-изоборнил-4,6-диметилфенол (7), т.пл. 81-82 °С (82.9-83 °C) [19] синтезировали из 2,4-диметилфенола по методике.…”
Section: экспериментальная частьunclassified
“…Chlorophyll a and its derivatives, especially methylpheophorbide a, are a promising basis for the synthesis of biologically active substances, such as photosensitizers for photodynamic therapy of cancer [1][2][3][4] and microbial diseases, [4,5] diagnostic drugs for oncology, [4] hybrid antioxidants [6][7][8][9] and others. The conjugation of a chlorin macrocycle with a fragment of the desired structure allows to assign the necessary properties for the molecule as a whole.…”
Section: Opening Of Exocycle In the Methyl Pheophorbide A Amide Derivmentioning
confidence: 99%
“…We have previously shown that the amidation of the ester group at position 13(2) of the methyl pheophorbide a exocycle is a convenient way of forming an amide bond having a significant synthetic potential. [6][7][8][9][10][11][12][13][14] The use of this reaction is a convenient way of synthesizing the conjugates of methylpheophorbide a and its analogs with terpenophenols, [6][7][8][9] introducing bulk alkyl substituents, [10,11,13] as well as obtaining dimeric and trimeric chlorophyll a derivatives. [12,14] The hydrolysis of the 17-substituent ester group in such conjugates is of interest from the viewpoint of hydrophilizing the resulting derivatives, as well as further chemical modification using the carboxyl group reactions.…”
Section: Opening Of Exocycle In the Methyl Pheophorbide A Amide Derivmentioning
confidence: 99%